Principle of tolerance in kazakh аnd turkic akyn- zhyrau’s work (Journal of Philosophy Culture and Political Science, 2015)
Today in Kazakhstan focuses on the spiritual education of the historicaltraditions. Especially the principle of tolerance has become a fundamentalaspect of moral education. Great poets who stand at the originsof literary art Abai, Shakarim, Maylykozha, Budabay even in their difficulttimes sang of the unity of peoples. Also in the works of the Turkish poetsand Shaiyr there are many reasons about the importance of tolerance. Inparticular, in his writings eastern poets Maulana Rumi, Zhunis Amire perceivedtolerance important part of religion. Thus, the continuity of unanimitypassed on from the older generation to the younger. It has laid downthe foundation of a common mentality and outlook of the Turkic peoples.In this article we consider the principle of tolerance in the works of Kazakhand Turkish akyns-zhyrau.
Keywords: tolerance; akyns and zhyrau; kindness; spirituality.